2012
DOI: 10.1152/ajpgi.00167.2012
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of swallow-induced cortical BOLD positive and negative fMRI activity

Abstract: Functional MRI (fMRI) studies have demonstrated that a number of brain regions (cingulate, insula, prefrontal, and sensory/motor cortices) display blood oxygen level-dependent (BOLD) positive activity during swallow. Negative BOLD activations and reproducibility of these activations have not been systematically studied. The aim of our study was to investigate the reproducibility of swallow-related cortical positive and negative BOLD activity across different fMRI sessions. We studied 16 healthy volunteers util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 57 publications
1
27
0
Order By: Relevance
“…Functional EPI scans were acquired over 34 contiguous 4-mm thick sagittal slices over the whole brain volume in an interleaved fashion without any gap or overlap, with a slice-wise pixel resolution of 64 × 64 pixels over a 240 mm field of view yielding a within-slice resolution of 3.75 × 3.75 mm, captured with an echo time (TE) of 23.4 ms and a repetition time (TR) of 2000 ms.At the end of the second scan session, a separate paradigm driven functional scan was performed, which was strictly used to independently identify cortical and subcortical areas activated with swallowing in order to use them as seed regions for FC analysis ( functionally guided connectivity analysis ). Details of the imaging parameters and analytical techniques of this “seed finder” scan have been previously described (Babaei et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Functional EPI scans were acquired over 34 contiguous 4-mm thick sagittal slices over the whole brain volume in an interleaved fashion without any gap or overlap, with a slice-wise pixel resolution of 64 × 64 pixels over a 240 mm field of view yielding a within-slice resolution of 3.75 × 3.75 mm, captured with an echo time (TE) of 23.4 ms and a repetition time (TR) of 2000 ms.At the end of the second scan session, a separate paradigm driven functional scan was performed, which was strictly used to independently identify cortical and subcortical areas activated with swallowing in order to use them as seed regions for FC analysis ( functionally guided connectivity analysis ). Details of the imaging parameters and analytical techniques of this “seed finder” scan have been previously described (Babaei et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Scientific articles were categorized specific features to the swallowing cortical representation (3,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) . Research on elderly and patients with dysphagia underwent compared to control groups.…”
Section: Population Studiedmentioning
confidence: 99%
“…A chronological analysis of the presented studies, observed that initially the concern was the confirmation of cortical activation mechanisms for swallowing Therefore, procedures such as saliva (1,3,5,7,(16)(17)(18)(19)(20)22,23,26,(29)(30)(31)(32) , water (5,11,12,17,(24)(25)(26)28,29,31) , barium (5,26,29,31) swallowing were performed, comparing swallow and not swallow (1,7,14,27) . Later on, studies began to analyze differences in the cortical areas, responsible for each motor phase, differentiating the role of the structures involved.…”
Section: Tasks Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a consistent ensemble of brain regions (sensorimotor, cingulate and insular cortices, lateral prefrontal and parietal regions) has been identified in governance of deglutition 51, 52 , the specific role of distinct brain regions and their interactions await further study. Functional connectivity of swallowing network and interactions of involved brain regions has just been recently described for resting state and during swallowing 53-55 .…”
mentioning
confidence: 99%